Pengaruh Kepemimpinan dan Konten Pekerjaan Terhadap Kinerja Karyawan melalui Motivasi sebagai Variabel Intervening (Studi Kasus Pada Karyawan CV. Cita Nasional Semarang) - Muhammad Haris Fakri; Widiartanto Widiartanto (Universitas Diponegoro, 2017)
Nowadays , business competition in the industrial sector is very competitive. Human resources is one of the main factors to compete with the other company. CV.Cita Nasional is one of milk processing industry company in Semarang, Central Java. Problems in this research is performance reduction of production employee 2013-2015, This was happen due to less leadership and job content that is not in suits with employees. This study attempts to find out whether there is impact of leadership and job content to employees performance by motivation on production employees CV.Cita Nasional. Data collection techniques used the interview and questionnaires , while the sample techniques used non probability of sampling with 94 the total sample. The research results show that leadership and job content having a positive influence and significantly to employee performance by motivation. This can be seen from the results of the simple analysis linear regression, multiple linear regression, t test, the coefficients determination test , sobel test and path analysis. Motivation as variable intervening mediate between leadership against employee performance that is both partial mediation as well as motivation as variable intervening mediate between leadership against employee performance that is both full mediation.